Burnout and Engagement's Relationship to Drug Abuse in Lawyers and Law Professionals. Issue 7 (16th July 2022) - Ogbonnaya, Uchenna C.; Thiese, Matthew S.; Allen, Joseph
Abstract : This research investigated the relationships between drug abuse and both occupational burnout and engagement among law professionals. These data empower clinicians to consider the complex relationships between the two separate constructs of burnout and engagement as they relate to drug abuse among law professionals and other high similar professional occupations. Abstract : Objective: Investigate the associations between drug abuse and the prevalence of the engagement and burnout dichotomy in law professionals. Methods: Eligible participants completed a questionnaire where odds ratios of drug abuse and other confounding variables and their association to engagement or burnout were calculated using multiple logistic regression. Results: When looking at all law professionals, burnout is a statistically significant predictor for drug abuse ( P = 0.04, not shown). Law professionals whose burnout scores fell in the highest bin have 4.71 (95% CI [1.38–16.08]) times higher odds of having a problem with drug abuse than those whose burnout scores fell in the second bin. Conclusion: Study findings showed a possible way to affect the prevalence of drug abuse in law professionals by affecting the engagement and burnout dichotomy.